HAS THE ECONOMY OF JAPAN IMPROVED BY ABENOMICS? - Kudratov , Shokhrukhbek (Innovative Development in Educational Activities, 2023)
This research discusses the economic policy program of Japanese Prime Minister Shinzo Abe, known as “Abenomics”. Abenomics is based on three core principles that are often referred to as the “Three Arrows”. By Mr. Abe’s terminology—that is, the “bold monetary policy,” the “flexible fiscal policy,” and the “growth strategy” (Wakatabe, 2015). The main goals of this policy are to take the economy out of continuous deflation, to depreciate the yen (JPY), and to reach an inflation rate target of 2 % per year (Fukuda, 2013). This study aims to analyze whether the economy of Japan improved by Abenomics by examining the conditions of small and medium-sized enterprises (SMEs) in Japan after its onset. The research advances two hypotheses: the number of small and medium sized enterprises bankruptcies decreased after December 2012 and the exporting sector shows a relatively low level of decline in the bankruptcy number among Japanese firms. After implementing the new policy, the Japanese economy improved firms and made more profit, and bankruptcies among SMEs decreased.